THE RELATIONSHIP BETWEEN SELF-CONCEPT, COPING -STRATEGIES FOR STRESS AMONG WORKERS DURING COVID - Prinyapol, Penprapa (JOURNAL OF HUMANITIES AND SOCIAL SCIENCES SONGKHLA RAJABHAT UNIVERSITY, 2022)
This research aimed to study the relationship between self-concepts-and coping strategies on stress among workers during COVID. The sample group consisted of 107 working people in the three southern border provinces, yielding a response rate of 93 % calculated by the G*Power software program using a simple random sampling technique and online data collection. The research instrument was a questionnaire including (1) the personal data, (2) the self-concept scale, (3) the coping strategies scale, and (4) the stress scale, which is a 5-level Likert scale. The results were as follows 1) the workers’ reported a high level of self-concept; 2) their problem solving and social support-seeking were at a high level while the avoidance coping was at a moderate level; 3) their overall stress levels were high; 4) self-concept was positively correlated with the level of stress significantly at 0.01 level, 5) avoidance coping was negatively correlated with stress significantly at 0.05 level. 6) self-concept and coping strategies could predict workers’ stress level about 11%.